A Study of Nusantara Arba‘īn Hadith Literature: Genealogy, Characteristics, and the Dynamics of Its Composition - Saputra, Doni; Wendry, Novizal; Hidayat, Ahmad Taufik (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2025)
Historical evidence shows that Hadith literature in the Nusantara experienced a revival and golden age in the 20th century, marked by the emergence of arba‘īn-style compilations. This article aims to investigate the genealogy of the structure and themes found in these arba‘īn works. Employing historical and content analysis methods, the study follows three key stages: data reduction, display, and interpretation. The analysis was supported by the ATLAS.ti application as an analytical tool. The findings reveal that during the 20th century, three notable arba‘īn-style works emerged: at-Tarmasī’s collection of 22 Tṡulāṡiyyāt al-Bukhārī hadiths; Hāsyim Asy‘arī’s compilation, intended as ethical and devotional guidance for members of Nahdlatul Ulama (NU); and al-Fadānī’s compilation of 40 hadiths sourced from 40 different books and scholars. These works laid the foundational model for arba‘īn-style hadith writing in the Nusantara. The thematic focuses of the texts also vary: at-Tarmasī emphasizes the virtues of religious practices, Hāsyim Asy‘arī highlights the Prophet Muhammad’s moral teachings, and al-Fadānī concentrates on Islamic legal principles governing human relations with God and all living beings.